Facile one-pot hydrothermal synthesis and electrochemical properties of carbon nanospheres supported Pt nanocatalysts. (27th July 2016) - Yang, Yi; Luo, Lai-Ming; Du, Juan-Juan; Li, Shan-Shan; Zhang, Rong-Hua; Dai, Zhong-Xu; Zhou, Xin-Wen
Abstract: One kind carbon nanosphere supported Pt nanocatalyst (Pt/CN-1) has been successfully synthesized by a facile one-pot hydrothermal synthesis using sucrose as carbon source and triblock pluronic copolymer P123 as reducer and stabilizer. The obtained Pt nanoparticles with an average diameter at 3.0 nm were uniformly distributed on the surface of the carbon nanospheres. The other kind Pt/CN-2 was prepared through the same route just in absence of P123, the carbon sphere was used as both carrier and reducer due to its reducing nature. Characterization demonstrated that the Pt/CN-2 was aggregated seriously without the protection of P123. The electrocatalytic tests indicated that the Pt/CN-1 nanocatalyst exhibited an enhanced electrocatalytic activity toward methanol oxidation in acidic media than that of Pt/CN-2 catalyst and commercial Pt/C catalyst. The promising synthetic method provides a new avenue to prepare carbon spheres supported Pt-based nanocatalysts used for direct alcohols fuel cells (DAFCs). Highlights: Carbon nanospheres supported Pt nanocatalyst was prepared by a hydrothermal process. The reduction of Pt nanoparticles and carbonization of sucrose was happened at the same time. The catalysts exhibit an enhanced catalytic properties than that of commercial Pt/C catalyst.